Good Governance: From State Civil Servants into Government Employment Agreement (PPPK) - Dicky Maryono (Universitas Sultan Ageng Tirtayasa, 2022)
According to the ASN Law, State Civil Apparatus includes Civil Servants, also known as ASN, and Government Employees with Work Agreements, also known as PPPK. The repercussions of utilizing APBN or APBD cannot be separated from the management of PPPK. As a result, the management of human resource management must be considered. As a result, the purpose of this research is to examine the good governance of human resource management among government employees with work agreements (PPPK). The descriptive qualitative research approach was employed, with data collected through interviews, documentation, and observation. According to the study's findings, the purpose of hiring government employees with a work agreement is to provide services and perform responsibly in order to portray good governance. Government employees with work agreements will not only be able to wait for the government to make efforts to enhance their performance, but they will also be able to produce breakthroughs that will increase their quality or performance in realizing good governance.